Functional mitral regurgitation: an overview for surgical management framework - Nappi, Francesco; Avatar Singh, Sanjeet Singh; Santana, Orlando; Mihos, Christos G. (Journal of Thoracic Disease; Vol 10, No 7 (July 31, 2018): Journal of Thoracic Disease, 2018)
Functional mitral regurgitation (FMR) is one the most common complications of myocardial infarction (MI) in adults carrying a significant clinical and economic burden. Despite specific randomized controlled studies to address its treatment have been performed, there are still a number of questions remained unanswered. Outcomes of surgical repair of FMR are still hampered by a significant rate of recurrence of regurgitation and need for reoperation. Mechanisms underlying failure of repairs still need to be completely clarified and questions regarding the indications and optimal timing for intervention as well as the best suitable operative technique to be applied are still debated. This work will review the current knowledge on FMR including its pathogenic mechanisms, the available treatment strategies, the evidences from trials and observational studies and the potential future directions to address the issues related to its treatment.